Strategi keberlanjutan kegiatan jasa pengolahan limbah medis melalui pendekatan SWOT - Wuri, Imaniar Septa Kencana; Tumuyu, Sri Setiawati; Utomo, Suyud Warno (Jurnal Pengelolaan Lingkungan Berkelanjutan (Journal of Environmental Sustainability Management), 2026)
The surge in medical waste generation following the Covid-19 pandemic, limited treatment facilities, and the expansion of healthcare services have driven the need for more integrated and sustainable waste management systems. This study aims to analyze the impact of medical waste treatment services on air quality and community involvement, as well as to formulate sustainability strategies. A mixed-method approach was used for data collection and analysis, while strategy formulation was conducted using SWOT analysis. Conducted at PT X, a medical waste management service industry located in Polokarto District, Sukoharjo Regency, Central Java Province. The study found that air quality from medical waste processing activities complied with quality standards. However, community participation remains low, and corporate social responsibility (CSR) programs are not yet oriented toward community development, resulting in suboptimal long-term benefits. The strategies needed based on the results of the SWOT analysis are technological intervention with environmentally friendly fuel substitution, enhancing CSR innovation towards community development, and building a landfill facility.